Solving integrated berth allocation and crane assignment problem using a tabu search metaheuristic - Şuvak, Zeynep. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2013., 2013)
The volume of container transportation and the throughput rate at terminals has been increased vastly in recent years. Container terminal operators have to utilize their limited resources efficiently in order to cope with the rising demand while satisfying the expectations of vessel operators. The management of integrated quayside operations is the primary concern of this study. Hence, two models one of which integrates berth allocation and quay crane (number) assignment problems (BACAP), and the other uni es berth allocation and speci c quay crane assignment problems (BACASP) are provided. A tabu search algorithm and local improvement procedures are implemented to solve BACAP and the method is tested on 3 different instance groups which are generated where vessels arrive with changing frequencies. A quay crane schedule is obtained by solving the shortest path problem on the graph representation of a BACAP solution. As a consequence, TS algorithm given for BACAP is modi ed to a solution method for BACASP by incorporating the shortest path problem into the metaheuristic. The TS algorithm for BACASP is justi ed on the test instances which are previously generated for BACAP.
Keywords: Heuristic algorithms.